High‐Quality Plasmonic Materials TiN and ZnO:Al by Atomic Layer Deposition. Issue 10 (6th August 2021) - Izyumskaya, Natalia; Fomra, Dhruv; Ding, Kai; Morkoç, Hadis; Kinsey, Nathaniel; Özgür, Ümit; Avrutin, Vitaliy
Abstract : Electromagnetic radiation when coupled to collective oscillations of free electrons, dubbed as plasmonics, makes it possible to manipulate light at dimensions well below the diffraction limit and substantially enhances light–matter interaction. Plasmonics has already enabled many novel technologies with a wide variety of application in chemical and biosensing, medical treatments, nonlinear and quantum optics, metamaterials, optical nanotweezers, nanolasers, solar cells, light‐emitting diodes, and telecommunications. Coating the well‐established semiconductor circuitry with metals, such as Au and Ag, imparts the stack with much coveted plasmonic properties, but the metals suffer from high dissipative losses, limited optical tunability, and poor mechanical, chemical, and thermal stabilities, which render them undesirable. Emerging alternative plasmonic materials, such as TiN and ZnO:Al, overcome these limitations and offer wide tunability of their electrical and optical properties. Among a wide range of techniques used for the preparation of TiN and ZnO:Al thin films, atomic layer deposition (ALD) offers advantages such as conformity, scalability, and low growth temperature, which makes this technique the most suitable for the integration of plasmonics with the complementary metal–oxide–semiconductor (CMOS) electronics. Herein, a brief review of recent advances in ALD‐grown TiN and ZnO:Al thin films as pertained to plasmonic applications is given. Abstract : The emerging plasmonic materials titanium nitride and aluminum‐doped zinc oxide offer wide tunability of their electrical and optical properties and provide a possibility to overcome the shortcomings of common plasmonic metals, such as high dissipative losses and poor mechanical, chemical, and thermal stability. An overview of the recent advances in atomic layer deposition (ALD) of these materials for plasmonic applications is presented.